Membangun Kesadaran Anti Korupsi di Kelurahan Pamona : Sosialisasi pada Anak Usia Dini, Remaja dan Masyarakat - Fredrik Bastian Kawani; Selda Wilau; Riska Trivena Ladinggo; Marsela Gitania Elsa Mba; Olvina E.A Sangkalabu; Rosniawan Lelen Pokiro; Devayana Madamba Pole; Nansi Delia Nggowi; Jefli Henok Pombaela; Marsela Yudhit Lagurue; Marsel Brayen Siwagi Mawo; Trifena Pekombei; Mikhael Jibrael Balo; Olvit Olniwati Kayupa (Lembaga Pengembangan Kinerja Dosen, 2025)
Corruption is one of the serious problems that hinders development and public welfare throughout Indonesia, including in the Pamona sub-district area. One of the efforts to prevent corruption is to start early through education and socialization that discusses the values of integrity, honesty and responsibility to all levels of society so that they will be aware of the dangers of anti-corruption and behave anti-corruption from an early age. In fact, corruption has actually occurred from the simplest things to more complex things. The purpose of this study is to increase public understanding of the dangers and impacts of corruption in social life. This study uses a quantitative approach method. The method used is internet searching, a method of collecting data in research conducted by searching for information on the internet through search engines. The results of this study indicate that this activity strengthens the culture of anti-corruption and builds collective awareness to create a clean and integrated village government environment.